EFEKTIVITAS MODEL STM (SAINS TEKNOLOGI MASYARAKAT) TERHADAP PEMAHAMAN SISWA PADA KONSEP ENERGI DAN PERUBAHANNYA DI SEKOLAH DASAR - Muhamad Firdaus, Fery (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
The research objective was to determine the influence of STM (Science Society Technology) of the elementary school students' understanding. The study was conducted in the second semester of academic year 2012-2013 at the State Primary School Cipaku 03 as the experimental group, and at the State Primary School Nangela as a control group. The research sample of 20 students from each group. During the research process, the experimental group was given STM (Science Society Technology), while the control group was given conventional learning. The approach used in this study is a quantitative approach with quasi experimental design method nonequivalent groups pretest-posttests. Data analysis was performed using t-test. 0.05 significance level. The results showed a significant difference between the scores of students' understanding of the experimental group and the control group. It also found that the STM (Science Society Technology) is more effective in improving students' understanding compared to conventional learning, so that the STM (Science Society Technology) can be an alternative to learning that can be applied in an effort to improve understanding of elementary school students.